The Effect of a Short Course of Tocolytic Indomethacin on Urinary Biomarkers in Premature Infants - El Samra, Ahmad; Mian, Ayesa; Lande, Marc; Wang, Hongyue; Guillet, Ronnie (American Journal of Perinatology, 2021)
Objective The aim of this study was to determine the effects of a 2-day prenatal course of indomethacin on the premature kidney as reflected by serum creatinine and urinary biomarkers.Study Design Urine of infants ≤32 weeks was collected for the first 14 days and analyzed for cystatin C, neutrophil gelatinase-associated lipocalin, osteopontin, β2 microglobulin, epidermal growth factor, uromodulin, and microalbumin. Bivariate analysis compared serum creatinine and biomarkers of exposed (INDO) and unexposed (CONT) subjects.Results Fifty-seven infants (35 CONT and 22 INDO) were studied. The cohorts were similar in gestational age, birthweight, race, gender, nephrotoxic medication exposure, and Apgar's scores. CONT had more dopamine exposure and included more pre-eclamptic mothers (p = 0.005). No difference in creatinine-based acute kidney injury or the log transformed mean, maximum, and minimum values of urinary biomarkers was detected.Conclusion Our findings suggest that a short course of tocolytic indomethacin does not result in neonatal acute kidney injury.Key Points
Keywords: acute kidney injury; prematurity; biomarkers; indomethacin